Covid-19 Impact on Greek Tourism Sector and the Implemented Policies - Briola, Konstantina; Briola, Helen (HAPSc Policy Briefs Series, 2022)
Tourism is one of the most important economic activities internationally and many countries (e.g. Portugal, Spain, Greece) are highly dependent on the tourism sector. Tourism has always been considered a priority sector in Greece and significant capital investments have been made over the years for its development. The pandemic has driven the global economy into a severe recession and many industries have been significantly affected by the measures taken, including the tourism industry. In response to this crisis, the Greek government, aiming to further develop the tourism sector and restore tourist flows to normal levels, used a series of measures. In this paper, we study the effects of the implemented policies on tourism during the pandemic. Our results indicate that the policies had a direct impact on the increase in tourism flows.